2019
DOI: 10.1016/j.jvscit.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic polymer embolization after thoracic endovascular aortic repair

Abstract: Hydrophilic polymer embolization is a rare complication after endovascular procedures that is currently underappreciated. Present understanding on this phenomenon relies on sparse case reports with histologic evidence of foreign polymers in end-organ tissue. Here, we report two deaths associated with hydrophilic polymer embolization after complex thoracic endovascular aortic repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Although hydrophilic polymer coatings have improved device and vessel trauma-associated morbidity and mortality, HPE has been attributed to various complications, including distal ischemia and, even, death after common aortic and cardiac procedures such as thoracic endovascular aortic repair and transcatheter aortic valve implantation. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 A review of the literature found many case reports of HPE secondary to percutaneous intervention. However, it is likely, given the broad scope of how this phenomenon presents clinically, that HPE is likely significantly underrecognized and subsequently underreported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although hydrophilic polymer coatings have improved device and vessel trauma-associated morbidity and mortality, HPE has been attributed to various complications, including distal ischemia and, even, death after common aortic and cardiac procedures such as thoracic endovascular aortic repair and transcatheter aortic valve implantation. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 A review of the literature found many case reports of HPE secondary to percutaneous intervention. However, it is likely, given the broad scope of how this phenomenon presents clinically, that HPE is likely significantly underrecognized and subsequently underreported.…”
Section: Discussionmentioning
confidence: 99%
“…HPE can be identified clinically as distal ischemic skin lesions, renal dysfunction, stroke, respiratory complications, mesenteric ischemia or infarction, and a wide variety of clinical sequelae depending on the location of polymer embolization. 1 , 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 Despite the presence of these reports, studies quantifying polymer shedding in the in vitro setting and direct comparisons between products are lacking. In vitro manipulation of a Fastracker-18 infusion microcatheter (Target Therapeutics) produced particulate that shared Gram stain properties found on autopsy in four cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HPE is a rarely reported complication of endovascular procedures [3] , whereby outcomes depend on the affected organ, ranging from spontaneous resolution to death due to occlusion of vessels in vital organs. The exact mechanism by which polymer material embolises is uncertain, but it involves several factors including irregularity of the endothelial wall, whereby the hydrophilic material 'sheds off' downstream.…”
Section: Discussionmentioning
confidence: 99%